2008
DOI: 10.1186/1471-2199-9-34
|View full text |Cite
|
Sign up to set email alerts
|

miR-Q: a novel quantitative RT-PCR approach for the expression profiling of small RNA molecules such as miRNAs in a complex sample

Abstract: Background: MicroRNAs (miRNAs) are small endogenous non-coding interfering RNA molecules regarded as major regulators in eukaryotic gene expression. Different methods are employed for miRNA expression profiling. For a better understanding of their role in essential biological processes, convenient methods for differential miRNA expression analysis are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 29 publications
0
95
0
1
Order By: Relevance
“…Previously, discrimination of let-7 homologs was achieved with TaqMan real-time RT-PCR assays, whereby after a miRNA-specific RT, a common reverse primer was used for PCR and a miRNA-specific TaqMan probe was required for discrimination (Chen et al 2005). Assays with a similar strategy, but without the use of fluorescent probes, suffered from a significantly poorer discrimination of the let-7 homologs (Raymond et al 2005;Shi and Chiang 2005;Sharbati-Tehrani et al 2008). We hypothesized and showed that the specificity of the assays can be dramatically enhanced by a hemi-nested miRNAspecific reverse PCR primer and do not require the use of a fluorescent probe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, discrimination of let-7 homologs was achieved with TaqMan real-time RT-PCR assays, whereby after a miRNA-specific RT, a common reverse primer was used for PCR and a miRNA-specific TaqMan probe was required for discrimination (Chen et al 2005). Assays with a similar strategy, but without the use of fluorescent probes, suffered from a significantly poorer discrimination of the let-7 homologs (Raymond et al 2005;Shi and Chiang 2005;Sharbati-Tehrani et al 2008). We hypothesized and showed that the specificity of the assays can be dramatically enhanced by a hemi-nested miRNAspecific reverse PCR primer and do not require the use of a fluorescent probe.…”
Section: Discussionmentioning
confidence: 99%
“…1). Initially, we noticed that in a number of previous reports (Chen et al 2005;Raymond et al 2005;Shi and Chiang 2005;Duncan et al 2006;Varkonyi-Gasic et al 2007;Sharbati-Tehrani et al 2008;Yang et al 2009), the reverse PCR primers were designed to anneal directly to the sequences in the RT oligonucleotide. To achieve specificity, a unique miRNA-specific fluorescent probe is required to discriminate the targets from the nonspecific amplicons (Chen et al 2005).…”
Section: Overview Of a Hemi-nested Real-time Rt-pcr Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…miR-Q RT-PCR-The miR-155 expression analysis was carried out by miR-Q, a method developed by Sharbati-Tehrani et al (25) for the expression analysis of miRNA by RT-PCR. The expression of miR-155 in OSCC samples was compared with normal tissues using the 2 Ϫ⌬⌬CT method and 5 S rRNA as a normalizing control (26).…”
Section: Methodsmentioning
confidence: 99%
“…Real Time PCR Detection of miR-21-Mature miR-21 was detected using the miR-Q method as described previously (30,31). In brief, 500 ng of total RNA was used for reverse transcription of mature miR-21 using TaqMan reverse transcription reagents (Applied Biosystems) with a specific reverse primer (RT6-miR-21, tgtcaggcaaccgtattcaccgtgagtggttcaaca).…”
Section: Methodsmentioning
confidence: 99%